(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to find empirical evidence about the implementation of enterprise resource planning (ERP) to implement company performance. The data used in this study is secondary data consisting of annual financial statements of companies listed on IDX for the 2016-2018 period with cross-section criteria. Furthermore, the data were analyzed using analysis using simple regression analysis. The results showed that the application of ERP had a significant positive impact on company performance generated by return on assets (ROA).